Case Report: Therapeutic biopsy guided targeted therapy improves visual acuity and prolongs survival in bilateral uveal metastases as the initial presentation of lung adenocarcinoma - Ou, Tongtong; Yang, Yiliu; Ren, Chengda; Lu, Fang (Frontiers in Medicine, 2025)
BackgroundAlthough uveal metastasis is common in lung cancer, reports of bilateral uveal metastasis as the initial symptom in lung adenocarcinoma patients undergoing intraocular biopsy are rare. Such cases typically portend poor outcomes, with a median survival of only 6.5 months. The current diagnostic gold standard involves intraocular biopsy (vitreous or choroidal), which carries significant risks, including tumor dissemination and retinal detachment. Crucially, these procedures are purely diagnostic, requiring additional interventions for local tumor control. This gap underscores the need for innovative strategies that integrate diagnosis, local therapy, and molecular profiling without compromising ocular function or survival outcomes.Case presentationA 40-year-old male patient presented to our hospital with blurred vision and hemianopia in his right eye. Ophthalmic examination revealed bilateral uveal masses. Subsequent CT and PET/CT scans identified lung cancer with multiple metastases. Percutaneous biopsy of the lung confirmed the diagnosis of stage 4B lung adenocarcinoma. Transscleral biopsy was performed on the tumor in the left eye without affecting vision, and its immunohistochemical results were consistent with lung adenocarcinoma. Following transscleral tumor therapy and EGFR-TKI therapy, the patient achieved a best corrected visual acuity (BCVA) of 20/20 in both eyes with controlled tumor progression, surviving with stable disease for 3 years.ConclusionThis case underscores that bilateral uveal metastasis, even with ciliary body involvement, can achieve exceptional survival and visual recovery through targeted therapy. This case suggests ocular biopsy and early molecular testing may refine management for similar patients. The unexpected treatment response warrants further studies on tumor-ocular microenvironment interactions.